Relative renal functions for children using 99mTC-DTPA and 99mTC-DMSA (Journal of Bangladesh Academy of Sciences, 2021)
Radionuclides are widely used to study the relative renal functions (RRFs) for kidney patients. This work reports the determination of the RRFs using the technetium-99m dimercaptosuccinic acid (99mTc-DMSA) and technetium-99m diethylenetriamine-pentaacetic acid (99mTc-DTPA) for children having kidney diseases. The two methods are then compared to find the choice of scintigraphy for a particular type of disease. A total of 65 child kidney patients of ages 5 months - 16 years were the representative samples of the study. The mean RRFs calculated with 99mTc-DTPA was found as  and respectively, for the left and right kidneys. On the other hand, the values are  and  respectively, using 99mTc-DMSA. a significant positive correlation () were found between the RRFs calculated with the two scanning methods in Pearson correlation analysis. In one way ANOVA test, we did not find any difference between the RRFs calculated with 99mTc-DTPA and 99mTc-DMSA between the left and right kidneys. In Bland-Altman Plots, no mean difference was found between the two scanning methods and the correlation limit lies between -13.5 and12.6. The present study suggests using a single method for a particular type of disease. 99mTc-DMSA is the primary choice for the evaluation of RRF since it is easy, inexpensive and also provides cortical morphology, renal scar and cyst evaluation. But for glomerular filtration rate and renogram curve, 99mTc-DTPA should be the obvious selection as 99mTc-DMSA fails to provide any information for these cases.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 109-119, 2020